Odpowiedzi

2009-12-20T14:01:05+01:00
A) 3x³+30x²+75x=0 /:3
x(x²+10x+25)=0
x(x+5)²
x1=0
x2=-5 (dwa razy)

b) 18x+12x²+2x³=0 /:2
x(x²+6x+9)=0
x(x+3)²=0
x1=0
x2=-3 (dwa razy)
c) 2x³-54=0 /:2
x³-27=0
x³=27 /∛
x=3

d) x³-5x²-14x=0
x(x²-5x-14)=0
Δ=25+56=81
√Δ=9
x1=5-9/2=-2
x2=5+9/2=7
x3=0

e) (x-1)(x+2)=(x-1)(x+4)
x²+x-2=x²+3x-4
2x=2
x=1

f) (x²+4)(x+8)=x²-16
(x²+4)(x+8)=(x-4)(x+4)
Brak rozwiązań wymiernych :)

g) x³-3x²-4x+12=0
z Hornera x=-2
(x+2)(x²-5x+6)=0
Δ=25-24=1
x1=5-1/2=2
x2=5+1/2=3
x3=-2
2009-12-20T14:01:33+01:00
Rozwiąż równania
a) 3x³+30x²+75x=0
3x(x²+10x+25)=0
3x(x+5)²=0
3x=0 v x+5=0
x=0 v x=-5
b) 18x+12x²+2x³=0
2x(x²+6x+9)=0
2x(x+3)²=0
2x=0 v x+3=0
x=0 v x=-3
c) 2x³-54=0
2(x³-27)=0
x³=27
x=3
d) x³-5x²-14x=0
x(x²-5x-14)=0
x=0 v x²-5x-14=0
x=0 v Δ=25+56=81 →√Δ=3
x₁=(5-3):2=1
x₂=(5+3):2=4
e) (x-1)(x+2)=(x-1)(x+4)
(x-1)(x+2)-(x-1)(x+4)=0
(x-1)(x+2-x-4)=0
-2(x-1)=0
x=1
f) (x²+4)(x+8)=x²-16
x³+8x²+4x+32=x²-16
x³+8x²+4x+32-x²+16=0
x³+7x²+4x+48=0
brak rozw
g) x³-3x²-4x+12=0
x²(x-3)-4(x-3)=0
(x-3)(x²-4)=0
(x-3)(x-2)(x+2)=0
x=3 v x=2 v x=-2
2009-12-20T14:13:10+01:00
A) 3x³ + 30x² + 75x = 0
x(3x² + 30x + 75) = 0
x=0 v 3x²+30x+75=0
Δ=900-900=0
x₀=-30/6 = -5

b) 18x + 12x² + 2x³ = 0
2x³ + 12x² + 18x = 0
x(2x² + 12x + 18) = 0
x=0 v 2x² + 12x + 18 = 0
Δ= 144-144 =0
x₀= -12/4 = -3

c) 2x³ - 54=0
2x² + x - 54 = 0
Δ=1- 4*2*(-54)
Δ=1+432=433
Δ=pierwiastek z 433
x₁=-1-pierw.z 433 / 4
x₂= -1+pierw.z 433 / 4

d) x³ - 5x²-14x=0
x(x²-5x-14)=0
x=0 v x²-5x-14=0
Δ=25-4*1*(-14)
Δ=25+56=81
pierw.z Δ=9
x₁= 5-9/1 = -4
x₂= 14

e) (x-1)(x+2)=(x-1)(x+4)
x² + 2x -x -2 = x² +4x -x -4
x² + 2x - x -2 - x² -4x + x +4 = 0
-2x +2 = 0
-2x = -2 / : (-2)
x = 1

f) (x² + 4)(x+8)= x²-16
x³ + 8x² +4x + 32= x² -16
x³ + 8x² +4x + 32 - x² +16 = 0
x³ + 7x² + 4x + 48=0

g) x³-3x²-4x+12=0
x² (x-3) -4(x-3)=0
(x² -4)=0 v (x-3)=0
x² = 4 x=3
x=2